Systematic review on phytochemicals structure and activity databases - Shyam G Ingle; Aniket K Gade; Ganesh B Hedawoo (Elsevier, 2024)
Background: Phytochemicals, natural compounds derived from plants, have garnered significant attention for their potential health benefits and therapeutic properties. The burgeoning interest in leveraging phytochemicals for drug discovery underscores the necessity for comprehensive and reliable databases to store and analyze their structural and activity data. Purpose: This systematic review aims to offer a comprehensive overview of existing phytochemicals structure and activity databases, focusing on their features, capabilities, and limitations. This work provides fundamental information and multidimensional perspectives from plant information sources for modern drug discovery. Study Design: The review presents an analysis of the availability of chemical structure and other pertinent information across the identified databases. The search involved electronic databases, such as PubMed, and Web of Science, as well as manual searching of reference lists of relevant articles and reviews from Google Scholar and other search repositories. Methods: A systematic search strategy is employed to identify relevant databases that focus on phytochemicals and their structural and activity data. A literature survey spanning the last 20 years was conducted, identifying over 60 distinct phytochemicals databases and collections, with emphasis on published databases. Moreover, databases that have become inaccessible over time, leading to a loss of phytochemicals data, are highlighted. Results: The review provides insights into the landscape of phytochemicals databases, delineating the diversity of available resources and their accessibility. During literature survey since 1994, this study identified over 60 distinct phytochemicals databases and collections from published sources. Among these, 49 are currently open access, ensuring accessibility to a broader audience. Additionally, 18 databases allow bulk downloading, facilitating extensive and efficient access to phytochemicals data. Conclusion: By synthesizing fundamental information from diverse plant information sources, this review aims to offer multidimensional perspectives for modern drug discovery. It underscores the importance of accessible, maintained, and reliable databases in advancing research and development efforts harnessing the potential of phytochemicals.